Gradual versus structural technological change in the transition to a low-emission energy industry: How time-to-build and differing social and individual discount rates influence environmental and technology policies - Christoph Heinzel; Ralph Winkler (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2006)
We develop a general equilibrium model to study the transition from an established polluting to a new clean energy technology. Therefore, we consider two distinctive features: (i) the creation of new productive capital exhibits a timeto-build property, and (ii) the social and individual rates of time preference differ. We derive necessary and sufficient conditions for investment in the new and for replacement of the established technology. We show that, in addition to the standard emission externality, a further market failure stemming from the differing discount rates arises, the extent of which positively depends on the time-lag in capital accumulation. Moreover, we show that in a mutually reinforcing way both market failures create less favorable circumstances for the introduction of the new technology compared to the social optimum. The paper thus provides an additional reason why environmental policy should be complemented by technology policy in the transition to a low-emission energy industry.
Keywords: H23; Q48; Q55; 330; energy industry; gradual vs. structural technological change; rate of time preference; time-to-build